PERAN SIKAP DALAM MEMEDIASI PENGARUH WEBSITE LAYOUT DESIGN TERHADAP NIAT BELI KEMBALI - Dharma Sunu, Putu Wisnawan; Setiawan, Putu Yudi (E-Jurnal Manajemen, 2020)
The purpose of this research is to know the relation between website layout design, attitude and repurchase intention. The research is targeting the customer of lazada.co.id who domiciled in Bali. Sample’s size of the research is 90 respondents with non-probability sampling method Process of collecting the respondent’s data is by distributing questionnaire. Partial Least Square and Sobel test are used or the instrument’s research. Result of analysis shown that direct relation between website layout design, attitude and repurchase intention have significant positive relation. While, the indirect relation, attitude able to be mediation variable that associated two variables, such as website layout design and repurchase intention. It describes repurchase intention will increase if positive attitude of lazada.co.id customer also increase as the impact of well display of website layout design. Keywords: website layout design, attitude, repurchase intention